Basic education and training priority on strategy of empowerment of micro and small industry of leather craft in Magetan regency. (February 2020) - Susilowati, L; C Fajri, A; Ashar, K; Susilo, S
Abstract: This study aims to determine the empowerment strategy of micro and small industries of leather craft in Magetan. By using the same data from 10 selected respondents from Department of Industry and Commerce (DISPERINDAG) Magetan Regency, the owner of micro and small industry of leather craft, and leather craft community. The analysis technique used Analytical Hierarchy Process (AHP). The AHP results show that there are four alternative fields that are the respondents, the first are human resources, the second are innovations, the third are productions and the last are marketing. Based on the results of AHP analysis, the alternative program in the whole program of empowerment of micro and small industries of leather craft in Magetan Regency are: 1) Basic education and training with Leather Hall and College, 2) Skill improvement, 3) introduction of new products, 4) training and creativity of production, 5) opening market opportunities through exhibitions and social media, 6) reduce sales tax for micro and small industries, 7) entrepreneurship training, 8) new production technology, 9) development of existing products, 10) provide galleries for the marketing of micro and small industries, 12) facilitate the procurement of raw materials.